Learn From Home Policy Implementation in Primary-Level Student During Academic Year 2020-2021 in Medan - Desi Saragih (International Journal Labs, 2023)
Using data from the Regional Education Office of Medan City and triangulating with Policy Actor from North Sumatera Education Quality Assurance (BPMP Sumut), this study explores the Learn From Home (BDR) Policy implementation in Medan City during the Academic Year of 2020-2021 with a qualitative assessment referred to guidelines from the Indonesia Ministry of Education, Culture, Research, and Technology (MoECRT) Minister Circular Letter No. 04/2020 and Secretary General Circular Letter No. 15/2020. Findings indicated that during the Academic Year of 2020-2021, 88% of Primary students participated in BDR Online (Daring), while 12% in BDR Offline (Luring), with a case of 786 untracked students in two sub-districts. Public Schools tend to have higher Student-Teacher ratios than Private Schools. Across sub-districts in Medan City, 75% (10,010 teachers) are Honorary teachers, and 25% (3,311 teachers) are State Civil Workers (ASN). Collectively, the Total of Students per Study Group (Rombongan Belajar/rombel) follows the Minister of Education and Culture Regulation No. 22/2016 concerning Process Standards for Primary and Secondary Education with a ratio of students-rombel between 21 to 28. At Public Schools, the ratio of students-rombel is slightly exceeded the suggested ratio, with the total number of students per rombel between 22-29. However, the findings mainly vary when comparing schools in the same sub-district or across the sub-district. Based on qualitative assessment findings indicated that Learn from Home (Belajar Dari Rumah) Policy implementation was misaligned in two areas; (1)Data collection on students' BDR situation and (2) students' admission (PPDB) mechanism.